Switching from Knowledge to Competence-Based Teachings: Biology Teachers’ Attitudes and Instructional Practices - Bizimana, Emmanuel; Mutangana, Dieudonné; Mwesigye, Adrian (European Journal of Mathematics and Science Education, 2023)
The study investigated the attitudes of Biology teachers towards the Biology Competence-Based Curriculum (BCBC) and their instructional practices at the lower secondary school level in Nyamagabe district, Rwanda. A descriptive survey design was adopted. Also, a purposive sampling technique was used to select 26 (16 male and 10 female) teachers of Biology. Data were collected using a questionnaire addressed to Biology teachers in selected schools and analyzed and presented in terms of frequencies, percentages, mean, and standard deviation. A one-way ANOVA was employed in the hypothesis testing. The findings indicated that these teachers had positive attitudes towards the implementation of BCBC. As for female ones, they had more positive attitudes towards BCBC implementation than the male ones. Considering those from boarding schools, they had a more positive attitude than the ones from day schools. Additionally, teachers with less teaching experience had more favorable attitudes than those with long experience. Teachers' age did not have any effect on their attitudes. The study also revealed that teachers of Biology rarely applied competence-based approaches in their teaching and assessment processes of students’ learning. It was inferred that the usage of CBC approaches differed significantly among teachers from boarding and day schools. The usage of CBC assessment methods did not differ significantly among teachers. From the findings, it was concluded that CBC seems not to be effectively implemented in the lower secondary schools under the study. Consequently, a recommendation was made to facilitate Biology teachers in schools with in-service training for professional development.
Keywords: Biology teachers; Competence-based teaching; Competence; Curriculum implementation; Teaching approach